Emerging B-Cell Therapies in Systemic Lupus Erythematosus - Bag-Ozbek A; Hui-Yuen JS (Dove Medical Press, 2021)
Ayse Bag-Ozbek,1 Joyce S Hui-Yuen2– 4 1Division of Rheumatology, Renaissance School of Medicine, Stony Brook University Medical Center, Stony Brook, NY, USA; 2Division of Pediatric Rheumatology, Steven and Alexandra Cohen Children Medical Center, New Hyde Park, NY, USA; 3Zucker School of Medicine at Hofstra/Northwell, Hempstead, NY, USA; 4Center for Autoimmune, Musculoskeletal, and Hematopoietic Diseases Research, Feinstein Institute for Medical Research, Manhasset, NY, USACorrespondence: Joyce S Hui-YuenDivision of Pediatric Rheumatology, Steven and Alexandra Cohen Children Medical Center, 1991 Marcus Avenue, Suite M100, New Hyde Park, NY 11040, USATel +1 516.472.3700Fax +1 516.472.3752Email jhuiyuen@nshs.eduAbstract: Systemic lupus erythematosus (SLE) is a chronic, multisystem, autoimmune disease of unknown etiology, whose hallmark is the production of autoantibodies. B cells are promising targets for novel SLE therapies. In 2011, belimumab (Benlysta®), a fully humanized monoclonal antibody inhibiting B-cell activation and proliferation, was the first medication in 50 years to be approved by the US Food and Drug Administration to treat adult SLE. This review discusses the current experience with B-cell-targeted therapies, including those targeting B-cell-surface antigens (rituximab, ocrelizumab, ofatumumab, obinutuzumab, obexelimab, epratuzumab, daratumumab), B-cell survival factors (belimumab, tabalumab, atacicept, blisibimod), or B-cell intracellular functions (ibrutinib, fenebrutinib, proteasome inhibitors), for the management of SLE. It focuses on ongoing clinical trials and real-world post-marketing use, where available, including their safety profiles, and concludes with our recommendations for B-cell-centric approaches to the management of SLE.Keywords: systemic lupus erythematosus, treatment, novel B-cell therapies, belimumab, rituximab, epratuzumab